Variation of photostability of DNA-sensitive styrylcyanine dyes caused by N-alkyl functionalization - Snihirova, Y. V.; Losytskyy, M. Yu; Kryvorotenko, D. V.; Kuperman, M. V.; Moshynets, O. V.; Yarmoluk, S. M.; Mokhir, Andriy; Kovalska, Vladyslava B. (Biopolymers and Cell, 2020)
Aim. Synthesis and characterization of benzothiazole-based styrylcyanines functionalized by different N-alkyl tail groups as potential photostable probes for nucleic acids (NA) detection. Methods. Chemical synthesis, absorption and fluorescence spectroscopy, irradiation with a visible light source, confocal microscopy. Results. Styrylcyanines are weakly fluorescent when free, but in the presence of NA they show emission intensity increase of up to 83 times; the most pronounced emission increase was observed for the dyes Sbt1 and Sbt3 bearing posi-tively charged N-alkyl tail group. Photostability of the dyes Sbt1 and Sbt3 when non-bound to NA is low while binding to DNA results in a strong increase in their photostability. Dyes with uncharged and negatively charged N-alkyl groups are more photostable when free, and DNA slightly affects their photostability. This is also due to low binding of dyes with negatively charged tail groups to DNA. Sbt1 brightly stains cytoplasm and nuclear components (probably nucleoli) of mesenchymal stem cells; therefore this dye may be used to visualize cytoplasmic RNA and nuclear RNA clusters. Conclusions. Variation of chemical nature of N-alkyl tail group allows to design styrylcyanines of different photostability. Functionalized styrylcyanine dyes may be used for detection of nucleic acids in solution and visualization of RNA-containing components in microscopy.
CRIS-Team Scopus Importer:2020-07-31
Keywords: Fluorescence; Microscopy; NA detection; Photostability; Styrylcyanines